The murder of Emmett Till [videorecording (DVD)] - Nelson, Stanley, 1951-; Braugher, Andre (PBS Home Video, 2004)
The murder of 14-year-old Emmett Till, a black boy who whistled at a white woman in a Mississippi grocery store in 1955, was a powerful catalyst for the civil rights movement. Although Till's killers were apprehended, they were quickly acquitted by an all-white, all-male jury and proceeded to sell their story to a journalist, providing grisly details of the murder. Three months after Till's body was recovered, the Montgomery Bus Boycott began.